2021
DOI: 10.1371/journal.pone.0248358
|View full text |Cite
|
Sign up to set email alerts
|

Higher albumin levels on admission predict better prognosis in patients with confirmed COVID-19

Abstract: Background Research surrounding COVID-19 (coronavirus disease 2019) is rapidly increasing, including the study of biomarkers for predicting outcomes. There is little data examining the correlation between serum albumin levels and COVID-19 disease severity. The purpose of this study is to evaluate whether admission albumin levels reliably predict outcomes in COVID-19 patients. Methods We retrospectively reviewed 181 patients from two hospitals who had COVID-19 pneumonia confirmed by polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 43 publications
10
62
1
2
Order By: Relevance
“…Kheir et al study showed higher albumin levels on admission were associated with significantly fewer adverse outcomes in COVID-19 patients. 7 A metanalysis done by Panagiotis et al demonstrated the presence of significantly lower serum albumin concentrations in COVID-19 patients with high disease severity or poor outcome which is supporting the results of our study. 8 Regarding the association with comorbidities, our study found that serum albumin levels was significantly lower in severe COVID-19 patients with diabetes and hypertension.…”
Section: Discussionsupporting
confidence: 92%
“…Kheir et al study showed higher albumin levels on admission were associated with significantly fewer adverse outcomes in COVID-19 patients. 7 A metanalysis done by Panagiotis et al demonstrated the presence of significantly lower serum albumin concentrations in COVID-19 patients with high disease severity or poor outcome which is supporting the results of our study. 8 Regarding the association with comorbidities, our study found that serum albumin levels was significantly lower in severe COVID-19 patients with diabetes and hypertension.…”
Section: Discussionsupporting
confidence: 92%
“…The low albumin has been associated with adverse outcomes in various other disease conditions [18][19][20][21][22][23], as well as in COVID-19 patients who were hospitalized [9,10,24]. Kheir et al concluded in their study that higher albumin level on admission was associated with favorable outcomes in hospitalized COVID-19 patients [11]. We hope this study will help understand the characteristics of COVID-19 who did not require hospitalization.…”
Section: Plos Onementioning
confidence: 87%
“…It binds with the reactive oxygen species (ROS) and reactive nitrogen species (RNS) produced during inflammation saving cellular injury [8]. Few studies found that low serum has a direct effect on mortality and worse complications in hospitalized COVID-19 patients [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Serum hypoalbuminemia at admission has been associated with a worse prognosis including the risk of hospital readmission 22 . Yeo et al, observed a direct correlation between the peak creatinine concentration during admission and the risk of readmission 10 .…”
Section: Discussionmentioning
confidence: 99%